Horrid Henry and the abominable snowman - Simon, Francesca; Ross, Tony (London : Orion, 2007)
Collects four stories featuring Horrid Henry, including the title selection in which Henry enters a snowman building competition and hopes to win a year's supply of ice cream.
Horrid Henry and the abominable snowman -- Horrid Henry's rainy day -- Moody Margaret's makeover -- Horrid Henry's author visit.
3.4
K-3
Keywords: Contests -- Juvenile fiction; Horrid Henry (Fictitious character) -- Juvenile fiction; Human behavior -- Juvenile fiction; Snowmen -- Juvenile fiction; Behavior -- Fiction; Contests -- Fiction; Horrid Henry (Fictitious character) -- Fiction; Snowmen -- Fiction; Contests -- Fiction; Horrid Henry (Fictional character) -- Fiction; Human behavior -- Fiction; Snow -- Fiction